KNOWLEDGE AND ATTITUDES TOWARDS ORAL HEALTH AMONG PARENTS AND TEACHERS IN IASSY, ROMANIA - Ioan DANILA; Lucia BARLEAN; Iulia SAVEANU; Livia MIHAILOVICI; Cristina COSTOREL (Romanian Dental Association for Education, 2013)
The objectives of our study were: (1) assessing knowledge level and attitudes towards oral health among children's mothers and teachers; (2) analyzing oral health care habits of mothers in relation to socio-economic status (SES); (3) evaluation of the impact of an educational program for parents and teachers in Iassy, Romania. Material and methods. The authors initiated in 2004 a two-year longitudinal, questionnaire-based study which included 375 mothers of 9-11 years old school children and 103 school teachers from 18 schools in Iassy. The subjects' knowledge level and attitudes towards oral health were reevaluated in 2006. Data were analyzed using the Statistica program, ANOVA, Scheffe, Pearson, Chi -square, and Gamma tests (p<0,05). Results. The level of knowledge and attitudes towards the factors incriminated in dental decay development was significantly higher in teachers compared to mothers. The educational program resulted in an increased number of mothers' positive answers referring to the role of sugar consumption in the dental decay (from 50,2%, in 2004 to 59,7%, in 2006 ), the role of fluoride and tooth brushing in preventing dental decay (from 58,2% to 64,2% and, respectively, from 90,8% to 95,7%) (p<0,05). Conclusions. The findings of this study revealed a positive relationship between mothers' SES and the level of knowledge and attitudes towards oral health. The impact of the oral health education program was positive and resulted in improved oral health care knowledge and attitudes of mothers and teachers.